Integrative Strategies in Epidemiology, Public Health, and Health Education for Strengthening Disease Prevention and Crisis Response Systems - Abdulhakeem Mohammed Ali Aldhubayi, Awad Fahd Al-Mutairi, Abdullah Saleh M Al kharaim, Sumayyah Mudhhi Mutlaq Alanazi, Abdulhakim Musaad Alabdulmunim, Fatimah Marzouq Alamri, Majdah Suliman Alenzi, Nawaf Hamoud Almohammadi (Journal of International Crisis and Risk Communication Research, 2024)
Global health systems face increasingly complex challenges that require comprehensive, multidisciplinary strategies to strengthen disease prevention and crisis response. This review explores the distinct and complementary roles of epidemiology, public health, and health education, emphasizing their integration in building resilient and sustainable health systems in the face of health crises and challenges. Epidemiologists provide critical data for disease surveillance and risk assessment, public health professionals translate these data into evidence-based policies, and health educators promote community understanding and adherence to these interventions. The review highlights the importance of collaboration between these disciplines, supported by emerging technologies such as artificial intelligence (AI) and big data, to ensure coordinated, data-driven, and community-centered responses to health crises. Recommendations include enhancing interdisciplinary collaboration, integrating AI into health systems, and promoting community engagement as a cornerstone of public health strategies.